Biblical inspirations and canonical foundations of education = Inspirations bibliques et fondements canoniques de l’éducation = Ispirazioni bibliche e fondamenti canonici dell’educazione - Přibyl, Stanislav (Philosophy & canon law, 2018)
The New Testament reports several Jesus’s logia about children that form a part of his preaching of the kingdom of God. Children are shown as examples to be emulated and accepted by his disciples. Such testimonies can be found in synoptic gospels. However, Paul in his grand Song of Love in the First Epistle to the Corinthians appreciates the fact that he matured into his adult age. To his disciples Jesus also proposes an ideal of abandoning family life in favor of radical discipleship, while in Paul’s epistles to the Colossians and Ephesians we find the then model of the family and of raising children which Christians accept, yet they are obliged to perfect it in a life which draws its strength from the faith in Christ. For Paul, a more adequate option is to live without a wife; however, those in marriage should be strictly monogamous and raise their children well. In the course of its history, the Catholic Church has acknowledged celibacy as the appropriate form of clerical life. The Canon Law regulation on marriage and on the basic parameters of educating the offspring still draws its inspiration from the practice of the beginnings of the Church as documented in the New Testament.